Cool polyester fiber and method for producing the same

CN122543185BActive Publication Date: 2026-10-23JIANGSU JIANGNAN HIGH POLYMER FIBER
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611039506.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-23
Estimated Expiration
2046-07-14

AI Technical Summary

Technical Problem

[0006]为了克服现有凉感聚酯纤维凉感持久性差、耐洗涤性不佳、湿态舒适性差的缺陷,本申请提供一种凉感聚酯纤维及其制备方法

Benefits of technology

本申请依托亲水改性共聚酯与半芳香族刚性聚酯在熔体粘度、分子刚性上的物性差异,借助熔融纺丝剪切-拉伸耦合场的诱导调控作用,使组分自发形成表层亲水富集、芯部刚性取向的功能分区结构,无需复杂的复合纺丝工艺,即可同步实现导湿排汗与轴向导热的双重功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of polyester fibers, and particularly discloses a cool-feeling polyester fiber and a preparation method thereof. The cool-feeling polyester fiber is prepared from the following raw materials in parts by mass: polyester chips 80-95 parts, hydrophilic modified copolyester 5-10 parts, semi-aromatic rigid polyester 4-12 parts and multi-functional epoxy chain extender 0.3-1.2 parts. The polyester fiber prepared by the application has excellent mechanical properties, and when used for a fabric, the polyester fiber has excellent moisture permeability and moisture conductivity and washing resistance while ensuring a good cool-feeling coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of polyester fibers, and more specifically, to a cool-feeling polyester fiber and a method for preparing the same. Background Technology

[0002] Polyester fiber boasts advantages such as high strength, excellent abrasion resistance, wrinkle resistance, shape retention, easy care, and low shrinkage, making it widely used in sportswear, outdoor textiles, and other fields. However, polyester fiber itself has poor moisture absorption and breathability. In high-temperature environments or when worn close to the skin for extended periods, sweat and heat generated by the human body cannot be dissipated in time, creating a humid and hot microenvironment on the fiber surface. This leads to discomfort such as stuffiness, stickiness, and dry, itchy skin, severely limiting its wearing comfort in summer and sports settings.

[0003] To address the stuffiness issue of polyester fibers, the industry has developed cooling polyester fibers. Currently, the mainstream manufacturing technologies fall into two main categories: The first category is inorganic powder thermal conductivity modification technology. This technology adds a high amount of nano-sized high thermal conductivity powders such as mica, jade, aluminum nitride, and alumina to the polyester matrix. The rapid thermal conduction of the powders quickly removes heat from the skin, achieving an "instant cooling sensation." For example, the patent application CN102031581A discloses a method for manufacturing ultra-cooling health-promoting polyester fibers. This technical solution has the following problems: First, the inorganic powders and organic polyester matrix are thermodynamically incompatible and easily agglomerate during melt blending, resulting in extremely poor dispersion uniformity. Second, the large, hard agglomerates formed not only severely wear down the screw and clog the spinneret orifices, reducing spinning stability and component lifespan, but also create stress concentration points within the fiber, significantly deteriorating the fiber's mechanical strength and thus affecting the quality and lifespan of the final product.

[0004] The second category is organic small molecule hygroscopic cooling modification technology. This technology achieves cooling by adding organic cooling agents rich in hydrophilic groups and utilizing the principle of heat absorption through water evaporation after moisture absorption. For example, patent application CN118880486A discloses a cooling polyester fiber, comprising 10-30 parts of a cooling-regulating additive and 100-220 parts of polyester chips; wherein the cooling-regulating additive is composed of an esterification product of mannitol and / or lactitol with at least one of p-aminobenzoic acid and its carboxylic acid derivatives, or salicylic acid and its carboxylic acid derivatives.

[0005] In this technical solution, the cooling effect relies entirely on the heat absorption of sweat evaporation. In high humidity environments, sweat evaporation is hindered, and the cooling performance is greatly reduced or even lost. At the same time, the small molecule cooling agent and the polyester matrix are only physically blended. They are prone to migration, precipitation, and loss during long-term use and multiple washing processes, resulting in poor cooling durability and short service life. Summary of the Invention

[0006] In order to overcome the shortcomings of existing cooling polyester fibers, such as poor cooling durability, poor washability, and poor wet comfort, this application provides a cooling polyester fiber and its preparation method.

[0007] This application provides a cooling polyester fiber, which is prepared from the following raw materials in parts by weight: 80-95 parts polyester chips, 5-10 parts hydrophilic modified copolyester, 4-12 parts semi-aromatic rigid polyester, and 0.3-1.2 parts multifunctional epoxy chain extender; The hydrophilic modified copolyester is prepared by co-condensation reaction of bis(2-hydroxyethyl) terephthalate, sodium dimethyl isophthalate-5-sulfonate, polyethylene glycol, and optionally 2,5-dihydroxyterephthalic acid. The semi-aromatic rigid polyester is prepared by a stepwise feeding method: first, dimethyl terephthalate is pre-esterified with a portion of ethylene glycol, then dimethyl 2,6-naphthalenedicarboxylate is added and esterified with the remaining ethylene glycol for further esterification, and finally polycondensation is performed to obtain the product.

[0008] In this scheme, the spinning shear-stretch coupling field can promote the efficient orientation of semi-aromatic rigid polyester along the fiber axis, forming rigid chain-enriched micro-regions that overlap to construct a near-continuous axial heat conduction pathway. Utilizing the differences in melt viscosity and molecular rigidity between the hydrophilic modified copolyester and the semi-aromatic rigid polyester, a differentiated distribution trend of components is formed under the melt spinning shear-stretch coupling field, achieving the distribution effect of enriched hydrophilic components on the surface and concentrated heat-conducting components in the core. At the same time, by using a multifunctional epoxy chain extender to covalently bond with the end groups of each component, the multiphase interface bonding state is optimized, reducing interface defects and interface thermal resistance, achieving synergistic optimization of cooling performance and mechanical properties, and effectively improving fiber washability and spinning process stability.

[0009] Preferably, the method for preparing the hydrophilic modified copolyester includes the following steps: Under an inert atmosphere, bis(2-hydroxyethyl) terephthalate, sodium dimethyl isophthalate-5-sulfonate, polyethylene glycol, and optional 2,5-dihydroxyterephthalic acid are added to a reactor in a mass ratio of (466~471):(8.5~11.5):(17.5~18):(0~7.5). Catalyst, stabilizer, and antioxidant are added, the temperature is raised to 220~225℃, and the reaction is carried out for 40~50 min. The vacuum is then drawn to 400~500 Pa, and the temperature is maintained for 10~15 min. The vacuum is then drawn again to 80~100 Pa, and the temperature is raised to 250~255℃. The reaction is carried out for 70~80 min, the material is discharged, granulated, and hydrophilic modified copolyester is obtained.

[0010] Preferably, the amount of catalyst used is 0.08% to 0.1% of the total mass of bis(2-hydroxyethyl) terephthalate and / or 2,5-dihydroxyterephthalic acid, sodium dimethyl isophthalate-5-sulfonate and polyethylene glycol.

[0011] Preferably, the amount of stabilizer is 0.02% to 0.03% of the total mass of bis(2-hydroxyethyl) terephthalate and / or 2,5-dihydroxyterephthalic acid, sodium dimethyl isophthalate-5-sulfonate and polyethylene glycol.

[0012] Preferably, the amount of antioxidant is 0.2% to 0.4% of the total mass of bis(2-hydroxyethyl) terephthalate and / or 2,5-dihydroxyterephthalic acid, sodium dimethyl isophthalate-5-sulfonate and polyethylene glycol.

[0013] In this design, the structure can create stable and dispersed hydrophilic microregions on the fiber surface, forming a continuous hydrophilic moisture-wicking network that quickly wicks away sweat from the skin, improving the sticky feeling when wet. The hydrophilic functional groups are covalently grafted onto the molecular backbone, making them difficult to migrate and detach, and exhibiting excellent water-washing stability. The core function of this component is to enhance breathability and comfort, and it can indirectly contribute slightly to the cooling sensation upon contact through sweat evaporation.

[0014] Preferably, the method for preparing the semi-aromatic rigid polyester includes the following steps: Under an inert atmosphere, dimethyl terephthalate and ethylene glycol are added to a reactor, along with some catalyst. The temperature is raised to 190-200°C, and the reaction is carried out for 1-1.5 hours. After adding dimethyl 2,6-naphthalenedicarboxylate and ethylene glycol, the remaining catalyst is added, and the temperature is raised to 200-210°C. The reaction is carried out for 1-1.5 hours. The system is then evacuated to 400-500 Pa and held at that temperature for 10-15 minutes. The system is then evacuated to 80-100 Pa and the temperature is raised to 250-255°C. The reaction is carried out for 120-150 minutes. The product is then discharged, granulated, and a semi-aromatic rigid polyester is obtained.

[0015] Preferably, the molar ratio of the total amount of dimethyl terephthalate, dimethyl 2,6-naphthalenedicarboxylate, and ethylene glycol is (0.7~0.8):(0.2~0.3):(2.2~2.6).

[0016] Preferably, the amount of catalyst used is 0.07% to 0.1% of the total mass of dimethyl terephthalate, dimethyl 2,6-naphthalenedicarboxylate, and ethylene glycol.

[0017] Preferably, the amount of stabilizer used is 0.02% to 0.03% of the total mass of dimethyl terephthalate, dimethyl 2,6-naphthalenedicarboxylate, and ethylene glycol.

[0018] In this scheme, the semi-aromatic rigid polyester obtained has excellent compatibility with the base polyester. The naphthalene ring rigid units continuously distributed in the molecular backbone can be efficiently oriented along the fiber axis under the spinning shear stretching field to form a rigid chain segment enrichment region. They overlap to construct an almost continuous axial heat conduction pathway, which can effectively improve the contact cooling performance of the fiber.

[0019] Preferably, the catalyst is tetrabutyl titanate.

[0020] Preferably, the stabilizer is trimethyl phosphate.

[0021] Preferably, the antioxidant includes antioxidant 1010 and antioxidant 168.

[0022] Preferably, the cooling polyester fiber further includes 0.5 to 1.2 parts by weight of a hydroxyl boron oxide heterocyclic oligomer, wherein the hydroxyl boron oxide heterocyclic oligomer is obtained by dehydration condensation of trimethylolpropane and boric acid.

[0023] Preferably, the method for preparing the hydroxyl-containing boron oxide heterocyclic oligomer includes the following steps: Under an inert atmosphere, trimethylolpropane and boric acid were added to a reactor at a molar ratio of (1.5~2.0):1, along with toluene and catalyst B. The mixture was heated to 110~120℃ and reacted for 3~4 hours. After cooling, washing, and drying, a hydroxyl-containing boron-oxygen heterocyclic oligomer was obtained.

[0024] In this scheme, by controlling the ratio of excess trimethylolpropane and using a moderate condensation process, complete cross-linking and end-capping of functional groups can be effectively avoided, ensuring that sufficient active sites are retained on the surface of the prepared boron-oxygen heterocyclic oligomer molecules. The unreacted boron hydroxyl groups in the molecule can undergo transesterification / esterification reactions with the terminal hydroxyl and carboxyl groups of the polyester molecular chain, forming partially stable BOC covalent bonds at the phase interface. This allows the oligomer to be uniformly dispersed in the polyester matrix, effectively improving the multiphase interface bonding state, reducing interfacial thermal resistance, and enhancing the thermal conductivity of the matrix interface. At the same time, it can also help optimize the fiber crystal structure.

[0025] Preferably, catalyst B is p-toluenesulfonic acid.

[0026] Preferably, the molar amount of catalyst B is 0.5% to 0.75% of the molar amount of trimethylolpropane.

[0027] Preferably, the cooling polyester fiber further includes 0.2 to 0.5 parts by weight of silanized nano-barium sulfate or silanized nano-boron nitride.

[0028] Preferably, the preparation method of the silanized barium sulfate nanoparticles or the silanized boron nitride nanoparticles includes the following steps: Nano-barium sulfate or nano-boron nitride is dispersed in a 3%–5% (w / w) silane coupling agent alcohol solution, the pH is adjusted to 4.0–5.0, the temperature is raised to 70–80°C, and the reaction is carried out for 4–5 hours. After solid-liquid separation, washing and drying, silanized nano-barium sulfate or silanized nano-boron nitride is obtained.

[0029] Preferably, the particle size distribution of the nano-barium sulfate is 30~80nm.

[0030] Preferably, the particle size distribution of the nano-boron nitride is 50~100nm.

[0031] Preferably, the silane coupling agent is silane coupling agent KH-560.

[0032] In this scheme, silanized nano-barium sulfate, as a nucleating agent, effectively improves the orientation and crystallinity of fiber spinning, reduces the thermal conductivity barrier, and enhances mechanical strength through particle reinforcement. Its intrinsic thermal conductivity is limited, primarily contributing to improved cooling sensation upon contact. Silanized nano-boron nitride possesses excellent intrinsic thermal conductivity and can overlap with rigid polyester thermal conductivity pathways within the matrix, directly strengthening the core thermal conductivity network. It is the core functional filler for improving cooling sensation upon contact. Both, after silane modification, exhibit good interfacial bonding with the matrix, reducing the degradation of mechanical and thermal conductivity properties caused by agglomeration.

[0033] Preferably, this application also provides a method for preparing a cooling polyester fiber, comprising the following steps: Cool-feel polyester fiber is obtained by melt processing polyester chips, hydrophilic modified copolyester, semi-aromatic rigid polyester and multifunctional epoxy chain extender, followed by spinning, cooling, stretching, crimping and heat setting.

[0034] In this scheme, under the action of high-temperature shear field and stretching field of melt spinning, the hydrophilic modified copolyester has a lower melt viscosity and contains hydrophilic groups, so it exhibits stronger fluidity in the high shear rate region (i.e., fiber surface) and tends to accumulate on the fiber surface; while the semi-aromatic rigid polyester has a large molecular chain rigidity and high melt viscosity, so it is mainly distributed in the fiber core and aggregates along the axial orientation under the stretching action to form an ordered rigid structure and construct axial heat conduction channels.

[0035] The epoxy groups in multifunctional epoxy chain extenders can form covalent bonds with the carboxyl or hydroxyl groups at the ends of polyester chips, hydrophilically modified copolyesters, and semi-aromatic rigid polyester molecular chains, reducing interfacial tension, significantly improving the interfacial bonding strength of multiphase interfaces, and ensuring the stability of component distribution structure during spinning, finishing, and long-term use. Combined with a profiled cross-section design, it can increase the specific surface area of ​​fibers, construct continuous capillary moisture-wicking channels, and synergistically optimize the fiber's moisture-wicking and overall heat dissipation performance.

[0036] Preferably, the melt processing is specifically performed by compounding and extrusion via a twin-screw extruder.

[0037] Preferably, the spinning temperature is 270~280℃ and the spinning speed is 3000~3200m / min.

[0038] Preferably, the spinneret of the spinning process has a cross-shaped, trilobal, Y-shaped, or irregular cross-section with longitudinal grooves.

[0039] Preferably, the cooling is side-blowing cooling, with an air temperature of 20~25℃ and an air speed of 0.4~0.6m / s.

[0040] Preferably, the stretching is a multi-stage stretching process, and the stretching temperature is 70~80℃.

[0041] Preferably, the heat setting is a relaxation heat setting, with a setting temperature of 120~130℃ and a setting time of 5~10min.

[0042] Preferably, when adding a semi-aromatic rigid polyester, the step of adding a hydroxyl boron oxide heterocyclic oligomer is also included.

[0043] Preferably, when adding a semi-aromatic rigid polyester, the step of adding silanized barium sulfate nanoparticles or silanized boron nitride nanoparticles is also included.

[0044] In summary, this application has the following beneficial effects: This application relies on the differences in melt viscosity and molecular rigidity between hydrophilic modified copolyester and semi-aromatic rigid polyester. By leveraging the induction and regulation effect of the melt spinning shear-stretch coupling field, the components spontaneously form a functional partition structure with hydrophilic enrichment on the surface and rigid orientation in the core. This achieves the dual functions of moisture wicking and axial heat conduction simultaneously without the need for complex composite spinning processes. Detailed Implementation

[0045] The present application will be further described in detail below with reference to the embodiments.

[0046] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.

[0047] The polyester chips are fiber-grade polyethylene terephthalate chips with an intrinsic viscosity of 0.64~0.66 dL / g.

[0048] In the following preparation examples and embodiments, before use, polyethylene glycol was placed in a vacuum oven and dried at 50°C and -0.095 MPa for 3 hours to remove adsorbed moisture, and then sealed for later use.

[0049] Preparation Examples 1-2: Hydrophilic Modified Copolyesters Preparation Example 1 The preparation method of the hydrophilic modified copolyester in this example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, and condenser, 471g of bis(2-hydroxyethyl) terephthalate, 11.5g of sodium dimethyl isophthalate-5-sulfonate, 17.5g of polyethylene glycol 600, 0.4g of tetrabutyl titanate, 0.1g of trimethyl phosphate, 0.5g of antioxidant 1010, and antioxidant 168 were added. 0.5g of the polymer was purged with nitrogen three times to replace the air in the reactor, maintaining a slightly positive nitrogen atmosphere. The temperature was raised to 220℃ and reacted at a constant temperature for 40 minutes until no obvious distillate was observed. After the reaction was completed, a vacuum was slowly drawn, and the vacuum level was gradually reduced to 500Pa within 30 minutes. This vacuum level was maintained for 10 minutes, and the vacuum was further drawn down to 100Pa. At the same time, the temperature was raised to 250℃ and reacted at a constant temperature for 80 minutes. After the reaction was completed, the vacuum was stopped, nitrogen was introduced to break the reactor, and the molten polymer was quickly extruded into a cold water bath to cool and solidify. The polymer was then cut into granules by a pelletizer and dried in a vacuum drying oven at 60℃ for 4 hours to obtain the hydrophilic modified copolyester product.

[0050] Preparation Example 2 The preparation method of the hydrophilic modified copolyester in this example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, and condenser, 466g of bis(2-hydroxyethyl) terephthalate, 7.5g of 2,5-dihydroxyterephthalic acid, 8.5g of sodium dimethyl isophthalate-5-sulfonate, and 18g of polyethylene glycol 600 were added. After stirring and mixing thoroughly, 0.5g of tetrabutyl titanate, 0.15g of trimethyl phosphate, 1g of antioxidant 1010, and antioxidant 168 were added. 1g of polymer was added, and nitrogen gas was introduced to replace the air in the reactor three times to maintain a slightly positive pressure nitrogen atmosphere. The temperature was raised to 225℃ and the reaction was kept constant for 50 minutes until there was no obvious distillate in the system. After the reaction was completed, the vacuum was slowly evacuated. The vacuum degree of the system was gradually reduced to 400Pa within 30 minutes and maintained at this vacuum degree for 15 minutes. The vacuum was then continued to be evacuated to 80Pa, and the temperature was raised to 255℃ and kept constant for 70 minutes. After the reaction was completed, the vacuum was stopped, nitrogen gas was introduced to break the reactor, and the molten polymer was quickly extruded into a cold water tank to cool and solidify. The polymer was then cut into granules by a pelletizer and dried in a vacuum drying oven at 60℃ for 4 hours to obtain the hydrophilic modified copolyester product.

[0051] Preparation Examples 3-4: Semi-aromatic rigid polyesters Preparation Example 3 The preparation method of the semi-aromatic rigid polyester in this example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, and condenser, 1.4 mol of dimethyl terephthalate and 2.2 mol of ethylene glycol were added and stirred until homogeneous. Then, 0.35 g of tetrabutyl titanate and 0.14 g of trimethyl phosphate were added, and the mixture was heated to 190°C and reacted at this temperature for 1 hour. Next, 0.6 mol of dimethyl 2,6-naphthalenedicarboxylate, 2.2 mol of ethylene glycol, and 0.15 g of tetrabutyl titanate were added, and the mixture was stirred until homogeneous. The mixture was then heated to 200°C and reacted at this temperature for 1 hour. The reaction was then complete. Then, the vacuum was slowly reduced to 500 Pa within 30 minutes. The system was kept at this vacuum level for 10 minutes, and the vacuum was reduced to 100 Pa while the temperature was raised to 250°C. The reaction was carried out at this constant temperature for 120 minutes. After the reaction was completed, the vacuum was stopped, nitrogen gas was introduced to break the reactor, and the molten polymer was quickly extruded into a cold water bath to cool and solidify. The polymer was then cut into granules by a pelletizer and vacuum dried at 120°C and -0.095 MPa for 6 hours to obtain the semi-aromatic rigid polyester product.

[0052] The total mass of dimethyl terephthalate is 271.85g, the total mass of ethylene glycol is 273.11g, the total mass of dimethyl 2,6-naphthalenedicarboxylate is 146.54g, and the total mass of tetrabutyl titanate is 0.5g.

[0053] Preparation Example 4 The preparation method of the semi-aromatic rigid polyester in this example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, and condenser, 1.6 mol of dimethyl terephthalate and 2.6 mol of ethylene glycol were added and stirred until homogeneous. Then, 0.53 g of tetrabutyl titanate and 0.22 g of trimethyl phosphate were added, the temperature was raised to 200°C, and the reaction was maintained at this temperature for 1.5 h. Next, 0.4 mol of dimethyl 2,6-naphthalenedicarboxylate, 2.6 mol of ethylene glycol, and 0.2 g of tetrabutyl titanate were added, stirred until homogeneous, and the temperature was raised to 210°C, and the reaction was maintained at this temperature for 1.5 h. The reaction proceeded as follows. After the reaction, a vacuum was slowly drawn, and the vacuum level of the system was gradually reduced to 500 Pa within 30 minutes. This vacuum level was maintained for 15 minutes, and the vacuum was continued to be drawn to 100 Pa. At the same time, the temperature was raised to 255℃ and the reaction was kept at a constant temperature for 150 minutes. After the reaction was completed, the vacuum was stopped, nitrogen gas was introduced to break the reactor, and the molten polymer was quickly extruded into a cold water bath to cool and solidify. The polymer was then cut into granules by a pelletizer and vacuum dried at 120℃ and -0.095 MPa for 6 hours to obtain a semi-aromatic rigid polyester product.

[0054] The total mass of dimethyl terephthalate is 310.69 g, the total mass of ethylene glycol is 322.76 g, the total mass of dimethyl 2,6-naphthalenedicarboxylate is 97.70 g, and the total mass of tetrabutyl titanate is 0.73 g.

[0055] Preparation Examples 5-6: Hydroxyl Boronoxane Heteropolymers Preparation Example 5 The preparation method of the hydroxyl-containing boron-oxygen heterocyclic oligomer in this example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, water separator, and reflux condenser, 1.5 mol of trimethylolpropane and 1 mol of boric acid were added, along with 2 times the volume of toluene and 0.0075 mol of p-toluenesulfonic acid. After stirring and mixing thoroughly, the mixture was heated to 110°C and reacted for 3 hours. During the reaction, the water generated was continuously separated by the water separator. After the reaction was completed, the mixture was cooled, washed three times with deionized water, and toluene was removed by vacuum distillation. The mixture was then dried under vacuum at 60°C to constant weight to obtain a hydroxyl-containing boron-oxygen heterocyclic oligomer.

[0056] Preparation Example 6 The preparation method of the hydroxyl-containing boron-oxygen heterocyclic oligomer in this example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, water separator, and reflux condenser, 2.0 mol of trimethylolpropane and 1 mol of boric acid were added, along with 2 times the volume of toluene and 0.015 mol of p-toluenesulfonic acid. After stirring and mixing thoroughly, the mixture was heated to 120°C and reacted for 4 hours. During the reaction, the water generated was continuously separated by the water separator. After the reaction was completed, the mixture was cooled, washed three times with deionized water, and toluene was removed by vacuum distillation. The mixture was then dried under vacuum at 60°C to constant weight to obtain a hydroxyl-containing boron-oxygen heterocyclic oligomer.

[0057] Example 1 The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1600g polyester chips, 100g hydrophilic modified copolyester, 80g semi-aromatic rigid polyester, and 6g multifunctional epoxy chain extender.

[0058] Among them, the hydrophilic modified copolyester was from Preparation Example 1; the semi-aromatic rigid polyester was from Preparation Example 3; and the multifunctional epoxy chain extender was BASF ADR 4400.

[0059] The method for preparing the cooling polyester fiber in this embodiment includes the following steps: The above-mentioned polyester chips, hydrophilic modified copolyester, semi-aromatic rigid polyester, and multifunctional epoxy chain extender were mixed evenly and fed into a twin-screw extruder for melt mixing. The temperatures of each section of the twin-screw extruder were set as follows: Zone 1 260℃, Zone 2 270℃, Zone 3 275℃, Zone 4 275℃, Zone 5 270℃, and Die head 268℃. After mixing, the melt was fed into a spinning device for spinning at a spinning temperature of 280℃ and a spinning speed of 3200m / min. A cross-shaped spinneret was used, and side-blowing cooling was used during the spinning process. The side-blowing air temperature was 20℃ and the air speed was 0.6m / s. The cooled filaments underwent multiple drawing processes, with a total draw ratio of approximately 4.0 times and a drawing temperature of 80℃. After drawing, the fibers were crimped and then fed into a relaxation heat setting device, where they were set at 120℃ for 10 minutes to obtain cool-feeling polyester fibers.

[0060] Example 2 The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1900g polyester chips, 200g hydrophilic modified copolyester, 240g semi-aromatic rigid polyester, and 24g multifunctional epoxy chain extender.

[0061] Among them, the hydrophilic modified copolyester was from Preparation Example 1; the semi-aromatic rigid polyester was from Preparation Example 3; and the multifunctional epoxy chain extender was BASF ADR 4400.

[0062] The method for preparing the cooling polyester fiber in this embodiment includes the following steps: The above-mentioned polyester chips, hydrophilic modified copolyester, semi-aromatic rigid polyester, and multifunctional epoxy chain extender were mixed evenly and fed into a twin-screw extruder for melt mixing. The temperatures of each section of the twin-screw extruder were set as follows: Zone 1 260℃, Zone 2 270℃, Zone 3 275℃, Zone 4 275℃, Zone 5 270℃, and Die Head 268℃. After mixing, the melt was fed into a spinning device for spinning at a spinning temperature of 275℃ and a spinning speed of 3100m / min. A cross-shaped spinneret was used, and side-blowing cooling was used during the spinning process. The side-blowing air temperature was 25℃ and the air velocity was 0.4m / s. The cooled filaments underwent multiple drawing processes, with a total draw ratio of approximately 4.0 times and a drawing temperature of 75℃. After drawing, the fibers were crimped and then fed into a relaxation heat setting device, where they were set at 130℃ for 5 minutes to obtain cool-feeling polyester fibers.

[0063] Example 3 The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, and 18g multifunctional epoxy chain extender.

[0064] Among them, the hydrophilic modified copolyester was from Preparation Example 2; the semi-aromatic rigid polyester was from Preparation Example 4; and the multifunctional epoxy chain extender was BASF ADR 4400.

[0065] The method for preparing the cooling polyester fiber in this embodiment includes the following steps: The above-mentioned polyester chips, hydrophilic modified copolyester, semi-aromatic rigid polyester, and multifunctional epoxy chain extender were mixed evenly and fed into a twin-screw extruder for melt mixing. The temperatures of each section of the twin-screw extruder were set as follows: Zone 1 255℃, Zone 2 265℃, Zone 3 270℃, Zone 4 270℃, Zone 5 265℃, and Die Head 263℃. After mixing, the melt was fed into a spinning device for spinning at a spinning temperature of 270℃ and a spinning speed of 3000 m / min. A cross-shaped spinneret was used, and side-blowing cooling was used during the spinning process. The side-blowing air temperature was 25℃ and the air speed was 0.4 m / s. The cooled filaments underwent multiple drawing processes, with a total draw ratio of approximately 4.0 times and a drawing temperature of 70℃. After drawing, the fibers were crimped and then fed into a relaxation heat setting device, where they were set at 120℃ for 10 minutes to obtain cool-feeling polyester fibers.

[0066] Example 4 The difference between this embodiment and embodiment 3 is as follows: The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, 10g hydroxyl boron oxide heterocyclic oligomer, and 18g multifunctional epoxy chain extender.

[0067] The hydroxy boron oxide heterocyclic oligomer was derived from Preparation Example 5.

[0068] In the preparation method of the cooling polyester fiber in this embodiment, a hydroxyl boron oxide heterocyclic oligomer is added when a semi-aromatic rigid polyester is added.

[0069] Everything else is the same as in Example 3.

[0070] Example 5 The difference between this embodiment and embodiment 3 is as follows: The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, 24g hydroxyl boron oxide heterocyclic oligomer, and 18g multifunctional epoxy chain extender.

[0071] The hydroxy boron oxide heterocyclic oligomer was derived from Preparation Example 6.

[0072] In the preparation method of the cooling polyester fiber in this embodiment, a hydroxyl boron oxide heterocyclic oligomer is added when a semi-aromatic rigid polyester is added.

[0073] Everything else is the same as in Example 3.

[0074] Example 6 The difference between this embodiment and embodiment 3 is as follows: The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, 4g silanized nano barium sulfate, and 18g multifunctional epoxy chain extender.

[0075] The preparation method of silanized barium sulfate nanoparticles includes the following steps: Barium sulfate nanoparticles with a particle size distribution of 30-80 nm were added to a 3% (w / w) aqueous solution of silane coupling agent KH-560 in ethanol (the volume ratio of anhydrous ethanol to deionized water was 9:1). The solution was then transferred to an ultrasonic device and ultrasonically dispersed for 15 min at a power of 200 W and a frequency of 20 kHz. The pH was adjusted to 4.0 using 8% (w / w) glacial acetic acid. After stirring until homogeneous, the solution was heated to 70 °C and stirred at a constant temperature for 4 h. After the reaction was completed, the solution was allowed to cool naturally to room temperature. The solid product was collected by centrifugation, washed three times with anhydrous ethanol, dried in a vacuum drying oven at 80 °C for 6 h, ground, and sieved to obtain the silanized modified barium sulfate nanoparticles.

[0076] In the preparation method of the cooling polyester fiber in this embodiment, silanized nano-barium sulfate is added when adding semi-aromatic rigid polyester.

[0077] Everything else is the same as in Example 3.

[0078] Example 7 The difference between this embodiment and embodiment 3 is as follows: The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, 4g silanized nano boron nitride, and 18g multifunctional epoxy chain extender.

[0079] The preparation method of silanized boron nitride nanoparticles includes the following steps: Nano-sized boron nitride with a particle size distribution of 50-100 nm was added to a 3% (w / w) aqueous solution of silane coupling agent KH-560 in ethanol (the volume ratio of anhydrous ethanol to deionized water was 9:1), with a solid-liquid ratio of 1 g:10 mL. The solution was then transferred to an ultrasonic device and ultrasonically dispersed for 15 min at a power of 200 W and a frequency of 20 kHz. The pH was adjusted to 4.0 using 8% (w / w) glacial acetic acid. After stirring evenly, the solution was heated to 70 °C and stirred at a constant temperature for 4 h. After the reaction was completed, the solution was allowed to cool naturally to room temperature. The solid product was collected by centrifugation, washed three times with anhydrous ethanol, dried in a vacuum drying oven at 80 °C for 6 h, ground, and sieved to obtain the silanized modified nano-boron nitride product.

[0080] In the preparation method of the cooling polyester fiber in this embodiment, silanized boron nitride nanoparticles are added when adding semi-aromatic rigid polyester.

[0081] Everything else is the same as in Example 3.

[0082] Example 8 The difference between this embodiment and embodiment 3 is as follows: The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, 10g silanized nano boron nitride, and 18g multifunctional epoxy chain extender.

[0083] The preparation method of silanized boron nitride nanoparticles includes the following steps: Nano-boron nitride with a particle size distribution of 50-100 nm was added to a 5% (w / w) aqueous solution of silane coupling agent KH-560 in ethanol (the volume ratio of anhydrous ethanol to deionized water was 9:1), with a solid-liquid ratio of 1 g:10 mL. The solution was then transferred to an ultrasonic device and ultrasonically dispersed for 15 min at a power of 200 W and a frequency of 20 kHz. The pH was adjusted to 5.0 using 8% (w / w) glacial acetic acid. After stirring evenly, the solution was heated to 80 °C and stirred at a constant temperature for 5 h. After the reaction was completed, the solution was allowed to cool naturally to room temperature. The solid product was collected by centrifugation, washed three times with anhydrous ethanol, dried in a vacuum drying oven at 80 °C for 6 h, ground, and sieved to obtain the silanized modified nano-boron nitride product.

[0084] In the preparation method of the cool-feeling polyester fiber in this embodiment, silanized nano boron nitride is added when adding semi-aromatic rigid polyester.

[0085] Everything else is the same as in Example 3.

[0086] Example 9 The difference between this embodiment and embodiment 8 is as follows: The cooling polyester fiber of this embodiment is prepared from the following raw materials: 1800g polyester chips, 160g hydrophilic modified copolyester, 200g semi-aromatic rigid polyester, 10g silanized nano boron nitride, 24g hydroxyl-containing boron-oxygen heterocyclic oligomer, and 18g multifunctional epoxy chain extender.

[0087] In the preparation method of the cool-feeling polyester fiber in this embodiment, a hydroxyl-containing boron oxide heterocyclic oligomer and silanized nano boron nitride are added when a semi-aromatic rigid polyester is added.

[0088] The rest is the same as in Example 8.

[0089] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: The preparation method of the hydrophilic modified copolyester in this comparative example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, and condenser, 471g of bis(2-hydroxyethyl) terephthalate, 19g of polyethylene glycol 600, 0.4g of tetrabutyl titanate, 0.1g of trimethyl phosphate, 0.5g of antioxidant 1010, and 168 were added. 0.5g of the polymer was purged with nitrogen three times to replace the air in the reactor, maintaining a slightly positive nitrogen atmosphere. The temperature was raised to 220℃ and reacted at a constant temperature for 40 minutes until no obvious distillate was observed. After the reaction was completed, a vacuum was slowly drawn, and the vacuum level was gradually reduced to 500Pa within 30 minutes. This vacuum level was maintained for 10 minutes, and the vacuum was further drawn down to 100Pa. At the same time, the temperature was raised to 250℃ and reacted at a constant temperature for 80 minutes. After the reaction was completed, the vacuum was stopped, nitrogen was introduced to break the reactor, and the molten polymer was quickly extruded into a cold water bath to cool and solidify. The polymer was then cut into granules by a pelletizer and dried in a vacuum drying oven at 60℃ for 4 hours to obtain the hydrophilic modified copolyester product.

[0090] Everything else is the same as in Example 1.

[0091] Comparative Example 2 The preparation method of the semi-aromatic rigid polyester in this comparative example includes the following steps: In a nitrogen-protected reactor equipped with a stirrer, thermometer, and condenser, 1.4 mol of dimethyl terephthalate, 0.6 mol of dimethyl 2,6-naphthalenedicarboxylate, and 4.4 mol of ethylene glycol were added and stirred until homogeneous. Then, 0.5 g of tetrabutyl titanate and 0.1 g of trimethyl phosphate were added. The temperature was raised to 190°C and maintained for 1 hour. The temperature was then raised to 200°C and maintained for 1 hour. After the reaction was completed, a vacuum was slowly drawn, and the vacuum level of the system was gradually reduced to 500 Pa within 30 minutes. This vacuum level was maintained for 10 minutes, and the vacuum level was further reduced to 100 Pa while the temperature was raised to 250°C and maintained for 120 minutes. After the reaction was completed, the vacuum was stopped, and nitrogen gas was introduced to break the reactor. The molten polymer was quickly extruded into a cold water bath to cool and solidify. The polymer was then cut into granules by a pelletizer and vacuum dried at 120°C and -0.095 MPa for 6 hours to obtain a semi-aromatic rigid polyester product.

[0092] Everything else is the same as in Example 1.

[0093] Comparative Example 3 The difference between this comparative example and Example 1 is as follows: No semi-aromatic rigid polyester was added; Everything else is the same as in Example 1.

[0094] Performance testing The cooling polyester fibers obtained in Examples 1-9 and Comparative Examples 1-3 were woven into plain weave fabrics of the same specifications, and the following performance tests were conducted: (1) Cooling sensation coefficient: According to GB / T 35263-2017, a cooling sensation tester was used; the plain weave fabric sample was equilibrated for 24 hours at 23±2℃ and 50%±5% relative humidity, and the cooling sensation coefficient Q was tested. max ; (2) Moisture permeability: According to GB / T 12704.1-2009, the airflow velocity above the sample is 0.3~0.5m / s, and the relative humidity of the environment is 50%±2%; (3) Washing resistance: Plain weave fabric samples were washed 50 times according to GB / T 8629-2017, then hung to dry, and the contact cooling coefficient after washing was tested. (4) Fiber mechanical properties: According to GB / T 14344-2022 (filament), the fiber tensile tester was used, the clamping distance was 500±1mm, the stretching rate was 250mm / min, and the pre-tension was 0.15cN / dtex.

[0095] Table 1. Performance test data of cool-feeling polyester fibers obtained in Examples 1-9 and Comparative Examples 1-3

[0096] The analysis of the detection data in Table 1 is as follows: In Examples 1-3, by optimizing the amount of hydrophilic modified copolyester and semi-aromatic rigid polyester, the moisture-wicking and perspiration-wicking capabilities and the cooling sensation upon contact of the fiber can be optimized simultaneously. The overall performance shows a gradual upward trend and good mechanical stability.

[0097] In Examples 3-5, hydroxyl-containing boron-oxygen heterocyclic oligomers optimize the multiphase interface bonding, reduce interphase interfacial thermal resistance to improve heat conduction efficiency, and simultaneously anchor each functional component through chemical bonding, effectively inhibiting component migration and loss during washing, significantly improving the long-term durability of performance. The optimized interfacial bonding also reduces interfacial defects, improves stress transfer efficiency, gradually increases fiber breaking strength, enhances system rigidity, and correspondingly reduces breaking elongation.

[0098] In Examples 3 and 6-8, the cooling performance of the fiber after compounding with silanized nano-thermal conductive fillers was significantly improved. Among them, nano-barium sulfate mainly improved the cooling sensation by optimizing the crystal structure through nucleation, while boron nitride directly strengthened the thermal conductivity pathway due to its intrinsic high thermal conductivity, resulting in a more significant improvement in cooling sensation. The inorganic fillers slightly squeezed the moisture conduction channels, resulting in a slight decrease in moisture permeability, while exerting a particle reinforcement effect to improve breaking strength and reduce breaking elongation.

[0099] In Examples 5-9, when hydroxyl-containing boron-oxygen heterocyclic oligomers are compounded with silanized boron nitride nanoparticles, they exhibit a significant synergistic effect. The boron-oxygen heterocyclic oligomers optimize the phase interface between the polyester matrix and the nanofiller through covalent bonding, reducing interfacial thermal resistance and further improving the continuity of the thermal conductivity pathway. This results in an instantaneous cooling sensation that is higher than the combined effect of single components. At the same time, the interfacial anchoring effect is stronger, and the retention rate of cooling sensation after washing is improved. The mechanical properties are also further enhanced due to the optimized interfacial bonding.

[0100] In Comparative Examples 1-3, the hydrophilic modified copolyester prepared using only polyethylene glycol as a single component had little effect on the cooling coefficient, but its moisture permeability was significantly reduced. Comparative Example 2, prepared using a one-step feeding method, showed a significant decrease in contact cooling performance. Comparative Example 3, without adding any semi-aromatic rigid polyester, showed a decrease in the cooling coefficient, but its moisture permeability was not significantly different from the baseline formulation.

Claims

1. A cooling polyester fiber, characterized in that, It is prepared from the following raw materials in parts by weight: 80-95 parts polyester chips, 5-10 parts hydrophilic modified copolyester, 4-12 parts semi-aromatic rigid polyester, and 0.3-1.2 parts multifunctional epoxy chain extender; The hydrophilic modified copolyester is prepared by copolymerization of bis(2-hydroxyethyl) terephthalate, sodium dimethyl isophthalate-5-sulfonate, polyethylene glycol, and optionally 2,5-dihydroxyterephthalic acid. The preparation method includes the following steps: under an inert atmosphere, bis(2-hydroxyethyl) terephthalate, sodium dimethyl isophthalate-5-sulfonate, polyethylene glycol, and optionally 2,5-dihydroxyterephthalic acid are mixed in a mass ratio of (466~471). Add (8.5~11.5): (17.5~18): (0~7.5) to the reactor, add catalyst, stabilizer and antioxidant, heat to 220~225℃, react for 40~50min, vacuum to 400~500Pa, keep warm for 10~15min, continue vacuuming to 80~100Pa, and heat to 250~255℃, react for 70~80min, discharge, granulate, and obtain hydrophilic modified copolyester; Semi-aromatic rigid polyester is prepared by a stepwise feeding method: first, dimethyl terephthalate is pre-exchanged with a portion of ethylene glycol, then dimethyl 2,6-naphthalenedicarboxylate is added and further exchanged with the remaining ethylene glycol, and finally polycondensation is performed. The preparation method includes the following steps: under an inert atmosphere, dimethyl terephthalate and ethylene glycol are added to a reactor, a portion of the catalyst is added, the temperature is raised to 190~200℃, and the reaction is carried out for 1~1.5h. After adding dimethyl 2,6-naphthalenedicarboxylate and ethylene glycol, the remaining catalyst is added, the temperature is raised to 200~210℃, and the reaction is carried out for 1~1.5h. The vacuum is then drawn to 400~500Pa, and the temperature is maintained for 10~15min. The vacuum is then further drawn to 80~100Pa, and the temperature is raised to 250~255℃, and the reaction is carried out for 120~150min. The product is then discharged, granulated, and the semi-aromatic rigid polyester is obtained.

2. The cooling polyester fiber according to claim 1, characterized in that, The molar ratio of the total amount of dimethyl terephthalate, dimethyl 2,6-naphthalenedicarboxylate, and ethylene glycol is (0.7~0.8):(0.2~0.3):(2.2~2.6).

3. The cooling polyester fiber according to claim 1, characterized in that, The cooling polyester fiber also includes 0.5 to 1.2 parts by weight of a hydroxyl boron oxide heterocyclic oligomer, which is obtained by dehydration condensation of trimethylolpropane and boric acid.

4. The cooling polyester fiber according to claim 3, characterized in that, The method for preparing the hydroxyl-containing boron-oxygen heterocyclic oligomer includes the following steps: Under an inert atmosphere, trimethylolpropane and boric acid were added to a reactor at a molar ratio of (1.5~2.0):1, along with toluene and catalyst B. The mixture was heated to 110~120℃ and reacted for 3~4 hours. After cooling, washing, and drying, a hydroxyl-containing boron-oxygen heterocyclic oligomer was obtained.

5. The cooling polyester fiber according to claim 1, characterized in that, The cooling polyester fiber also includes 0.2 to 0.5 parts by weight of silanized nano-barium sulfate or silanized nano-boron nitride.

6. A method for preparing the cooling polyester fiber as described in claim 1, characterized in that, Includes the following steps: Cool-feel polyester fiber is obtained by melt processing polyester chips, hydrophilic modified copolyester, semi-aromatic rigid polyester and multifunctional epoxy chain extender, followed by spinning, cooling, stretching, crimping and heat setting.

7. The method for preparing cool-feeling polyester fiber according to claim 6, characterized in that, When adding a semi-aromatic rigid polyester, the step of adding a hydroxy boron oxide heterocyclic oligomer is also included.

8. The method for preparing cool-feeling polyester fiber according to claim 6, characterized in that, When adding semi-aromatic rigid polyester, the process also includes the steps of adding silanized barium sulfate nanoparticles or silanized boron nitride nanoparticles.

Citation Information

Patent Citations

  • Method for producing super-refreshing cool-feel health care polyester fiber

    CN102031581A

  • Cool polyester fiber and preparation method thereof

    CN118880486A

  • Process for the preparation of a fiber, a fiber and a yarn made from such a fiber

    CN105452548A

  • Environment-friendly hydrophilic low-melting PET composite short fiber and preparation method thereof

    CN112981610A